Paraoxonase-1 activities in individuals with different HDL circulating levels: Implication in reverse cholesterol transport and early vascular damage - Cervellati, Carlo; Vigna, Giovanni Battista; Trentini, Alessandro; Sanz, Juana M.; Zimetti, Francesca; Dalla Nora, Edoardo; Morieri, Mario Luca; Zuliani, Giovanni; Passaro, Angelina (Atherosclerosis, 2019)
Epidemiological data showing that high-density lipoprotein cholesterol (HDL-C) is inversely associated with cardiovascular disease have led to the idea that cholesterol contained in this lipoprotein may be protective. Against, recent evidence suggests that the athero-protection from HDLs may result from other functions, unrelated to the carried cholesterol. HDL accessory proteins, such as paraoxonase 1 (PON1), have been suggested to endows HDL with antioxidant and anti-inflammatory properties and to contribute to the athero-protective function of the lipoprotein. We aimed to evaluate whether extreme fluctuation in HDL-C levels correlates with PON1 activity. Levels of PON1-related arylesterase and lactonase were assessed in subjects with primary hyperalphalipoproteinemia (HAL, HDL-C>90th percentile), hypoalphalipoproteinemia (HA, HDL-C<10th percentile) and controls. Cholesterol efflux capacity (CEC) through several pathways and other metabolic parameters and markers of vascular disease were also determined. Despite the marked change in HDL-C and Apoliprotein A1 (APO A1) (p < 0.001 for all comparisons), arylesterase and lactonase were only slightly increased in HAL compared with HA subjects (p < 0.05), but not vs. controls. This change in PON1 activities was no longer significant after adjustment for either HDL-C or APO A1. Both enzymatic activities were positively associated only with aqueous diffusion CEC (r = 0.318, p < 0.05 and r = 0.355, p < 0.05, respectively) and negatively with the presence of plaques (p < 0.05). We showed that extreme high/low HDL-C levels are not associated with equal increase/decrease in PON1 activities. This enzyme appears to contribute to the HDL role in reverse cholesterol transport and anti-atherosclerosis processes. Further investigation is required to corroborate our findings. [Display omitted] •HDL-associated PON1 could represent one of the determinants of the biological functions of this lipoprotein.•High/low HDL-C levels are not accompanied by proportional PON1 activity changes.•PON1 specific activity is lower in hyperalphalipoproteinemia patients than in Controls.•The combination PON1/Apo A-1 is inversely related to subclinical atherosclerosis.